2021
DOI: 10.2147/ijnrd.s295025
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Changes in Hemodialysis Patients with End-Stage Renal Disease: DTI Analysis Results and ALFF Analysis Results

Abstract: Introduction The current study aimed to depict intrinsic structural changes and the spontaneous brain activity patterns in voxel level in patients with end-stage renal disease (ESRD) undergoing hemodialysis (HD) by using diffusion-tensor imaging and resting-state functional magnetic resonance (MR) imaging with an amplitude of low-frequency fluctuations (ALFF) algorithm and their clinical relevance. Materials and Methods In the study, the diffusion-tensor imaging and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…But in our study, the ALFF values of the right precentral gyrus were increased, which may suggest that the damage of the precentral gyrus was in the early stage and the compensative effect of spontaneous brain activity. Our findings of ALFF analysis are supported by the previous researches in patients with ESRD (15,(22)(23)(24)36). Liang et al revealed that patients with ESRD with minimal nephron-encephalopathy showed decreased ReHo in the right IPL, medial frontal cortex, and left precuneus, and altered ReHo values in some brain regions were correlated with neuropsychological tests and serological results (15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But in our study, the ALFF values of the right precentral gyrus were increased, which may suggest that the damage of the precentral gyrus was in the early stage and the compensative effect of spontaneous brain activity. Our findings of ALFF analysis are supported by the previous researches in patients with ESRD (15,(22)(23)(24)36). Liang et al revealed that patients with ESRD with minimal nephron-encephalopathy showed decreased ReHo in the right IPL, medial frontal cortex, and left precuneus, and altered ReHo values in some brain regions were correlated with neuropsychological tests and serological results (15).…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, previous ALFF studies found that patients with ESRD have abnormal spontaneous brain activity (22)(23)(24). For instance, Luo et al found that the ALFF values of the left inferior parietal lobe (IPL), left superior parietal lobe, and left precuneus in peritoneal dialysis patients with ESRD were reduced (24).…”
Section: Introductionmentioning
confidence: 95%
“…The results suggested that the SCr and BUN levels in ESRD patients after HD treatment were relatively high. The previous studies showed that SCr and BUN were related to the damage of the brain function system in patients with ESRD [ 25 , 26 ]. After discussion, the main reason for the difference between this research and the previous results is that the patients also received HD treatment during the rs-fMRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rs-fMRI can detect low-frequency (0.01–0.08 Hz) fluctuations in blood-oxygen-level-dependent (BOLD) signals and can be used to investigate spontaneous neural activity at rest ( Barkhof et al, 2014 ). In hemodialysis patients, impaired functional integrity of extensive brain regions has been measured by using multiple analytical methods based on rs-fMRI, including regional homogeneity (ReHo), amplitude of low frequency fluctuation (ALFF), and functional connectivity (FC) ( Li et al, 2018 ; Chen et al, 2020 ; Hu et al, 2020 ; Guo et al, 2021 ). Although the above results were inconsistent due to the diverse population cohorts and methodologies used, a correlation between functional abnormalities and cognitive dysfunction was indicated.…”
Section: Introductionmentioning
confidence: 99%